Juridical review of the authority of the Indonesian consultative assembly after the amendments to the 1945 constitution - Yudin Yunus (Jurnal Hukum Volkgeist, 2020)
This research discusses the Juridical Review of the Authority of the Indonesian Consultative Assembly after the 1945 Constitution Amendment . The results of the study describe the applicable provisions with the facts that occur in the community regarding the authority of the People's Consultative Assembly after the amendment of Law D1945 which is very minimal as a major State institution compared to other State institutions . The research method used in this research is normative research method. The statutory approach and the historical approach are approaches using legislation and regulations . And the historical approach is to refer to historical principles the law on the authority of the MPR prior to the amendments to the 1945 Constitution . These principles can be found in scholarly views or legal doctrines . This study aims to analyze the authority of the people's deliberative assembly before and after the amendment of the 1945 Constitution , based on the prevailing laws and legal history , namely by providing clarity on the status of the State MPR institution which is still maintained by the State as the main State institution which only has 3 post authorities. amendment e 4 In Article 3 of the Constitution, namely: 1 Amending and stipulating the Constitution , 2. Inaugurating the President and / or Vice President 3. Dismissing the President and / or Vice President during their term of office according to the Constitution . Based on the results of the research, it is concluded that the authority of the People 's Consultative Assembly after the Amendment of the 1945 Constitution is very minimal, namely only 3 powers not to mention that all of these 3 powers are only ceremonial